Cricket (Gryllodes sigillatus) meal fed to healthy adult dogs does not affect general health and minimally impacts apparent total tract digestibility. (17th March 2020) - Kilburn, Logan R; Carlson, Anne T; Lewis, Elizabeth; Serao, Mariana C Rossoni
Abstract: Insects can serve as a novel high-quality protein source for pet foods. However, there is an absence of research investigating the use of insects in pet food. The study objective was to evaluate the apparent total tract digestibility and possible health effects of diets containing graded levels of cricket ( Gryllodes sigillatus ) meal fed to healthy adult dogs. Thirty-two adult Beagles were randomly assigned to one of four dietary treatments: 0%, 8%, 16%, or 24% cricket meal. Dogs were fed their respective diet for a total of 29 d with a 6-d collection phase. Fecal samples were collected daily during the collection phase to measure total fecal output as well as apparent total tract digestibility for dry matter (DM ), organic matter, crude protein, fat, total dietary fiber, and gross energy. Blood samples were taken prior to the study and on day 29 for hematology and chemistry profiles. Data were analyzed in a mixed model including the fixed effects of diet and sex. Total fecal output increased on both an as-is ( P = 0.030) and DM basis ( P = 0.024). The apparent total tract digestibility of each nutrient decreased ( P < 0.001) with the increasing level of cricket meal inclusion. All blood values remained within desired reference intervals indicating healthy dogs. Slight fluctuations in blood urea nitrogen ( P = 0.037) and hemoglobin ( P = 0.044) levels were observed but were not considered of biological significance. Even with the decrease in digestibility with the inclusion of cricket meal, diets remained highly digestible at greater than 80% total apparent digestibility. In conclusion, crickets were demonstrated to be an acceptable ingredient for dog diets.